Alfabetização, letramento e direitos políticos nas eleições brasileiras do século XIX: uma análise sobre a exclusão das pessoas analfabetas - Camila Cristina Azevedo Castro Teixeira (2024)
The general aim of this research is to examine the legal and practical conditions that guided the tensions and disputes over the political capacity of illiterate people, in the electoral reforms and in the administrative practice of 19th-century Brazilian elections, to better understand the relationship between political rights and the mastery of reading and writing. Considering the prolonged validity of the prohibition of enlistment and eligibility of illiterate people, who remain ineligible even today, the study of elections emerges as a crucial space for questioning the historical reproduction of an institutionalized will against this group and other minorities. The issue presented here is the treatment given to the political rights of Brazilian citizens who could not read, write, and/or sign in the 19th-century, marked both by the valorization of reading and writing and the emergence of prejudice against the illiterate. As sources, we used electoral legislation, annals of parliament, and periodic press news, available digitally, as well as works produced during the period and electoral documents accessed in physical archives. We tried to relate the History of Written Culture with approaches from Social History and Political History, which provided a theoretical foundation for our research, and to articulate elements of the General Theory of Law with these frameworks. In the face of possible contradictions in the current understanding of the disenfranchisement of the illiterate vote, especially in academic production, we aim to conduct more comprehensive reflections on the theme. Some studies attribute to the Saraiva Law the explicit prohibition of the illiterate vote; however, in the aforementioned legal text, illiterate people are not explicitly prohibited from voting. Nevertheless, although the explicit exclusion of the illiterate in Brazilian elections only occurred in the last decade of the 19th century, the complexification of electoral practices, characterized by the progressive introduction of written procedures and documents, from the ordinances of the Kingdom of Portugal to the 19th-century electoral reforms, seems to have influenced not only the definition of the voter profile, based on initial reading instruction, but also the configuration of the profile of electoral agents, based on literacy. With the emergence of a literate elite in the urban centers of Brazil in the 19th century, the ability to read and write became intrinsically linked to access to institutionalized power, manifested in the full exercise of citizenship. This process highlights the significant role of the written word in Brazilian society, to the extent of affecting the guarantee of rights for the majority of the population, who, at the time, was illiterate.